Problem of lumpy skin disease outbreak prevention and eradication - R. A. Krivonos; G. A. Dzhailidi; A. V. Mischenko; V. A. Mischenko; O. Yu. Chernykh; V. N. Shevkoplyas; S. G. Dresvyannikova; D. V. Kolomiyets; S. V. Tikhonov (Ветеринария сегодня)
The paper presents data on lumpy skin disease spread in the Russian Federation, Middle East, Azerbaijan, Armenia, Georgia, Greece, Bulgaria, Macedonia, Serbia, Albania, and Kosovo. It characterizes epidemic situation in the Republic of Dagestan in 2015. It also gives analysis of the OIE data on lumpy skin disease outbreaks in the Russian Federation in 2016. The paper summarizes experience in LSD outbreak eradication in a large dairy establishment in Tbilisi Rayon of the Krasnodar Krai.